2021
DOI: 10.3390/land11010008
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Abandoned Cropland and Socioeconomic Impact Factors in China: Multi-Level Analysis Model Based on the Farmer and District/County Levels

Abstract: At present, abandoned cropland has become a common phenomenon spreading to countries around the world. China has seen widespread abandoned cropland in recent years. However, there are extremely few empirical studies of cropland abandonment and influencing factors nationwide. In this study, survey data from 8071 farmer households in 14 Chinese provinces were used to analyze the degree of cropland abandonment in China and its spatial distribution. A multi-level model was constructed to quantitatively explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In contrast, this study incorporates dynamic distance-based social data into the analysis, explaining the differences in cropland abandonment across different stages using evolving social data. An important future direction for this research involves continuously optimizing and refining the established indicator system of driving factors while exploring the underlying mechanisms from a multi-stakeholder perspective [65,66]. This approach will facilitate more meticulous and precise analysis at the micro-level, further validating the findings of this study and providing firmer theoretical support and practical guidance for the development of related fields.…”
Section: Spatial-temporal Characteristics and Driving Factors Of Crop...mentioning
confidence: 89%
“…In contrast, this study incorporates dynamic distance-based social data into the analysis, explaining the differences in cropland abandonment across different stages using evolving social data. An important future direction for this research involves continuously optimizing and refining the established indicator system of driving factors while exploring the underlying mechanisms from a multi-stakeholder perspective [65,66]. This approach will facilitate more meticulous and precise analysis at the micro-level, further validating the findings of this study and providing firmer theoretical support and practical guidance for the development of related fields.…”
Section: Spatial-temporal Characteristics and Driving Factors Of Crop...mentioning
confidence: 89%
“…Existing research used the proportion of abandoned farmland in the total farmland to measure land abandonment (Deng et al, 2020;Jiang and Song, 2022). Land abandonment, including the land abandonment behaviour and land abandonment area, is the dependent variable concerned in this study.…”
Section: Dependent Variablementioning
confidence: 99%
“…Farmers' personal characteristics include age, gender, education level, marital status, health status, and the experience of migrant workers. Existing studies have shown the probability of abandoned land increases when farmers' age increases (Jiang and Song, 2022).…”
Section: Control Variablesmentioning
confidence: 99%
“…In the past few decades, CA has spread throughout China (Zhang et al, 2019). This issue has also attracted considerable academic and public attention, and some research has been conducted on identifying the CA state in China (Jiang & Song, 2021; Li et al, 2022), as well as revealing its determinants and consequences (Subedi et al, 2022b; Yan et al, 2016; Zhang et al, 2014), but few studies have explored and mapped CAR in China.…”
Section: Introductionmentioning
confidence: 99%